PENGARUH PENAMBAHAN ENZIM DAN WAKTU INKUBASI TERHADAP JUMLAH PROTOPLAS MESOFIL DAUN ANGGREK Dendrobium Sp - Edu Setiti Wida Utami (The East Java Biological Society, 1995)
This research was done in order to study of effect the supplementation of enzyme and incubation time for the protoplast quality leaf mesophyll Dendrobium sp. Protoplast can be used for culture protoplast, for somatic cross, biology research, and material for genetic manipulation. This research to make use of material was Dendrobium sp Orchid. Explant that to used was leaf mesophyll Dendrobium sp. For the protoplast isolation to used enzyme combination cellulase and maserozym (Onozuka R-10). Yakult JONSHA Co., Ltd., (Japan) with concentration cellulase : maserozym is (0.5; 0.05; 0.75; 0.075; 0; 0.1). leaf mesophyll Dendrobium sp. to get a soak in enzyme solution with incubation time 12-13 hours and 14-1 hours.the result shown that enzyme combination selulase and maserozym can be used for protoplast isolation leaf mesophyll Dendrobium sp Orchid. The best enzyme concentration to fit for isolation protoplast leaf mesophyll Dendrobium sp to be selulase 0.75% and maserozym 0.075% with incubation time 14-15 hours.